2013
DOI: 10.1186/1742-4933-10-38
|View full text |Cite
|
Sign up to set email alerts
|

Does aging affect the immune status? A comparative analysis in 300 healthy volunteers from France, Austria and Spain

Abstract: BackgroundAs the European population is getting older, there is growing need in scientific data on how to achieve healthy and successful aging. A decline in immune function with age is unanimously supported by many epidemiological and clinical observations, with a decrease in T-cell mediated function encompassing a large part of this alteration. In the EU-funded VITAGE project, the effects of aging on biomarkers of immune status are being studied in three European countries. According to strict inclusion/exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
19
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 56 publications
7
19
1
Order By: Relevance
“…In turn, in the Leiden 85 + study, only 2% of individuals aged 89 years who participated in the study showed an CD4/CD8 ratio < 1 compared with 20% in those between 70 and 81 years of age. The observed increase in the CD4/CD8 ratio with age was similar to the results obtained by Vasson et al [23] in the Austrian elderly but opposed to the results from Spanish or French population where a trend towards a decreasing CD4/CD8 ratio was observed. The differences between countries/regions can be related to lifestyle factors such as habits, nutrition, physical and mental activity.…”
Section: Discussionsupporting
confidence: 89%
“…In turn, in the Leiden 85 + study, only 2% of individuals aged 89 years who participated in the study showed an CD4/CD8 ratio < 1 compared with 20% in those between 70 and 81 years of age. The observed increase in the CD4/CD8 ratio with age was similar to the results obtained by Vasson et al [23] in the Austrian elderly but opposed to the results from Spanish or French population where a trend towards a decreasing CD4/CD8 ratio was observed. The differences between countries/regions can be related to lifestyle factors such as habits, nutrition, physical and mental activity.…”
Section: Discussionsupporting
confidence: 89%
“…In general, higher counts of intratumoral CD8 + T c cells have been related to a better prognosis in different types of cancer including HNSCC [14][15][16]. In addition, we observed a positive correlation between the CD4 + /CD8 + T-cell ratio and age in our healthy subjects (Additional file 1: Figure S1A), which is supported by the data of others [32]. This age-related increase of the CD4 + /CD8 + T-cell ratio was not seen in our group of cancer patients.…”
Section: Frequency and Number Of T C Cellssupporting
confidence: 90%
“…Previous studies indicate that the CD4:CD8 ratio increased with aging, and was associated with OS and inflammatory markers (e.g. CRP and IL-6) [50][51][52][53]. Similarly, previous studies indicate that the CMV seropositivity was strongly correlated to inverted CD4:CD8 ratio, and the amount of IgG antibodies to CMV specifically influenced this inversion [1][2][3][4]54].…”
Section: Discussionmentioning
confidence: 80%